Slow pace of life in tropical sedentary birds : a common-garden experiment on four stonechat populations from different latitudes - Wikelski, Martin; Spinney, Laura; Schelsky, Wendy; Scheuerlein, Alexander; Gwinner, Eberhard (My University, 2003)
It has been hypothesized that organisms living at different latitudes or in different environments adjust their metabolic activity to the prevailing conditions. However, do differences in energy turnover simply represent a phenotypic adaptation to the local environment, or are they genetically based? To test this, we obtained nestling stonechats (Saxicola torquata) from equatorial Kenya (0 degrees N), Ireland (51.5 degrees N), Austria (47.5 degrees N) and Kazakhstan (51.5 degrees N). Birds were hand-raised and kept in Andechs, Germany. We measured their resting metabolic rates (RMR) and locomotor activity at an age of ca. 14 months (July) and 20 months (January), when birds went through postnuptial moult (July), and neither moulted nor exhibited enlarged gonads or migratory activity (January). RMR was generally higher during moult, but differed among populations: RMR was lowest in the resident Kenyan birds, higher in mostly sedentary Irish birds, and highest in migratory Austrian and Kazakhstan birds. Thus our data demonstrate that even in birds kept from early life under common-garden conditions, the 'pace of life', as indicated by metabolic turnover, is lower in sedentary tropical than in north-temperate migratory individuals of the same species. Such intrinsically low energy expenditure in sedentary tropical birds may have important implications for slow development, delayed senescence and high longevity in many tropical organisms.
Keywords: resting metabolic rate; tropical birds; life history; pace of life; stonechat; 570